Tomato Chlorotic Spot Virus - Jane E. Polston; Erin Wood; Aaron J. Palmateer; Shouan Zhang (EDIS)
Tomato chlorotic spot virus (TCSV) is a tospovirus, similar to but distinct from other tospoviruses currently present in Florida. Like these viruses, TCSV is transmitted by thrips and is able to replicate in both the vector and the plant. TCSV was first reported in Florida in 2012 in tomato plants in Miami-Dade and Lee Counties, but it may have been in the state for several years. Prior to 2012, TCSV was only known to occur in Brazil and Argentina. It is not known how this virus was introduced into Florida. This 5-page fact sheet was written by Jane E. Polston, Erin Wood, Aaron J. Palmateer, and Shouan Zhang, and published by the UF Department of Plant Pathology, May 2013.